Arctique : enjeux, opportunités et défis - Quillérou, Emmanuelle; Jacquot, Mathilde; Cudennec, Annie; Bailly, Denis (CCSD, 2015)
International audience The Arctic is often thought of as the land of polar bears and explorers. There are already several industries operating in the Arctic, through the Arctic, or at the periphery of the Arctic Circle. Receding and thinning sea ice with climate change provides increased access to natural resources, shipping routes and touristic areas, thereby providing new opportunities for economic development in the Arctic. The rewards for operating in the Arctic are potentially extremely high and attractive, but at high financial, environmental and social costs in an environment which remains financially very risky. Some stakeholders have started securing access to Arctic resources, sowing the seeds for a ‘cold rush’. Such ‘cold rush’ has not materialised yet, slowed down because of high economic costs and political sensitivity. The main political challenge ahead is to successfully reconcile the different perspectives and interests in the Arctic. One option to facilitate this reconciliation is to build up existing institutional capacity in line with the pace of economic development. There is certainly strong potential for creating shared economic wealth and well-being. Actual choices made by Arctic industries and countries for economic development, coordination and cooperation for establishment of environmental and social safeguards within the coming years will shape what the future Arctic will look like. L'Arctique est, dans l’esprit collectif, associé aux ours polaires et aux explorateurs. Plusieurs industries opèrent cependant en Arctique, à travers l'Arctique, ou à la périphérie du cercle polaire arctique. La fonte de la banquise induite par le changement climatique ouvre l’accès aux ressources naturelles, aux routes maritimes et aux zones touristiques polaires, offrant ainsi de nouvelles opportunités de développement économique en Arctique. Ces opportunités sont extrêmement attractives avec des gains potentiels très élevés, mais pour des coûts financiers, environnementaux et sociaux possiblement ...